Ultrasound-diagnosed disorders in shoulder patients in daily general practice: a retrospective observational study - Ottenheijm, Ramon PG (BioMed Central, 2014)
BACKGROUND: Ultrasound imaging (US) is considered an accurate and widely available method to diagnose subacromial disorders. Yet, the frequency of the specific US-diagnosed shoulder disorders of patients with shoulder pain referred from general practice is unknown. We set out to determine the frequency of specific US-diagnosed shoulder disorders in daily practice in these patients and to investigate if the disorders detected differ between specific subgroups based on age and duration of pain. METHODS: A predefined selection of 240 ultrasound reports of patients with shoulder pain (20 reports for each month in 2011) from a general hospital (Orbis Medical Centre Sittard-Geleen, The Netherlands) were descriptively analysed. Inclusion criteria were: (i) referral from general practice, (ii) age ≥18 years, and (iii) unilateral shoulder examination. Subgroups were created for age (<65 years and ≥65 years) and duration of pain (acute or subacute (<12 weeks) and chronic (≥12 weeks)). The occurrence of each specific disorder is expressed as absolute and relative frequencies. RESULTS: With 29%, calcific tendonitis was the most frequently diagnosed disorder, followed by subacromial-subdeltoid bursitis (12%), tendinopathy (11%), partial-thickness tears (11%), full-thickness tears (8%) and AC-osteoarthritis (0.4%). For 40% of patients, no disorders were found on US. Significantly more full thickness-tears were found in the ≥65 years group. ‘No disorders’ was reported significantly more often in the <65 years group. The supraspinatus tendon was the most frequently affected tendon (72%). CONCLUSIONS: Calcific tendonitis is the most common US-diagnosed disorder affecting patients in general practice, followed by subacromial-subdeltoid bursitis, tendinopathy, partial- and full-thickness tears and AC-osteoarthritis. Full-thickness tears were diagnosed significantly more frequently in patients ≥65 years, while ‘no disorders’ was more frequently reported in patients <65 years. Our findings imply that patients can be stratified into diagnostic subgroups, allowing more tailored treatment than currently applied.